Multi-scale three-dimensional simulation of the solidification microstructure evolution in laser welding of aluminum alloys under dynamic spatial thermal cycling - Liangyuan Ren; Shaoning Geng; Ping Jiang; Chu Han; Jun Jin; Yu Wang; Xin Yu (Journal of Materials Research and Technology)
Laser welding process involves three-dimensional (3D) highly dynamic spatial thermal cycling that results in intricate microstructure evolution in different zones. Understanding of the 3D topological evolution of microstructure under spatial thermal cycling is crucial for effective control in solidification processes. In this paper, a 3D multiphase-field model combined with accelerated methods and multi-scale coupling algorithms was developed for high-precision prediction of the dynamic microstructure evolution in laser welding. The heat flow distribution during laser welding varied significantly, with the cooling rates of 1.7–1.9 × 104 K/s at the middle region and 7.5–9.0 × 104 K/s at the bottom region. Considering the effects of 3D heat flow, a large angle may appear between the grains' primary growth direction and the cross-sectional plane, thereby the ultimate morphology through 2D analysis may lead to distortion from reality. The simulation of 3D microstructure evolution during distinct regions results showed that the grains at the bottom region exhibited larger characteristic dimensions (Length/Height >2.5, Length/Width >2.0) and columnar shape, while the middle region tended to form equiaxed structures. The grain size statistics revealed that the grains in the middle region exhibited larger scale due to their smaller GR (G: temperature gradient, R: growth rate) values. The simulation results were in good agreement with the electro-back-scattered diffraction testing results and the theoretical analysis.